PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL (HKI) USAHA MIKRO KECIL MENENGAH (UMKM) DI KABUPATEN BOGOR DITINJAU DARI SUDUT PANDANG SYARIAH - Fitri Aulia; Ermi Suryani; Bayu Purnama Putra (SAHID BUSINESS JOURNAL, 2022)
Optimalization of Intellectual Property Rights (HKI) protection for Small and Medium Micro Enterprises (MSMEs) in Bogor Regency is not yet optimal. This can be seen from the large number of plagiarism practices (plagiarism) on MSME products. In addition, there are still many MSMEs that do not know the importance of IPR protection for the continuity of their business. IPR protection is very important for MSMEs to avoid plagiarism. That way, MSMEs can be protected in producing quality products and can compete in the global market. In this way, MSME product brands in Bogor Regency will be more well-known. This study aims to analyze IPR protection for MSMEs, especially in Bogor Regency. In addition, a review was carried out from a sharia point of view. This research is a qualitative research with data collection carried out through observation, interviews, especially with the Department of Trade and Industry of the Bogor Regency Government, with the Industrial Supervisory Section, and document studies. The results of the study show that the efforts of the Trade and Industry Office of the Bogor Regency Government in protecting IPR for MSMEs, are carried out through IPR Socialization and Assistance Process, also guided by the Ministry of Law and Human Rights of the central government or its representatives in West Java Province. No matter what these efforts are, there are always problems with the protection of IPR for MSMEs in Bogor Regency.